2017
DOI: 10.1016/j.foodchem.2016.08.134
|View full text |Cite
|
Sign up to set email alerts
|

Milk from cows grazing on cool-season pastures provides an enhanced profile of bioactive fatty acids compared to those grazed on a monoculture of pearl millet

Abstract: The demand for dairy products from grass-fed cows is driven, in part, by their more desirable fatty acid (FA) profile, containing more n-3 FA and conjugated linoleic acids (CLA) than conventionally produced dairy products. This study investigated the effects of pearl millet (PM) vs. cool-season pasture (CSP) on animal performance and milk FA in a grazing system. Eight Holstein dairy cows were used in a repeated measures design with four-week periods. Forage type had no effect on animal performance (estimated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(30 reference statements)
2
16
0
1
Order By: Relevance
“…On the other hand, several nutrients in dairy products might inhibit carcinogenesis. Dairy products are an excellent source of calcium [ 38 ] which was reported to be significantly associated with reduced endometrial cancer risk [ 6 , 38 ]. Calcium in dairy products may be a potential cancer prevention element through vitamin D, as it is highly correlated and metabolically tied to vitamin D [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several nutrients in dairy products might inhibit carcinogenesis. Dairy products are an excellent source of calcium [ 38 ] which was reported to be significantly associated with reduced endometrial cancer risk [ 6 , 38 ]. Calcium in dairy products may be a potential cancer prevention element through vitamin D, as it is highly correlated and metabolically tied to vitamin D [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procedures involving animals were approved by the University of Vermont Animal Care and Use Committee. This research is part of a larger study that has been previously reported (for details see Bainbridge et al, 2017 ). Briefly, five multiparous (parity: 3.0 ± 0.7 lactations) mid-lactation (171 ± 21 days in milk) Holstein dairy cows were used in a repeated measures design with three 28-day periods.…”
Section: Methodsmentioning
confidence: 98%
“…An electronic rising plate meter (Jenquip; Feilding, New Zealand) was used to estimate DM intake three times per week as described previously (Bainbridge et al, 2017 ). Weekly forage samples for quality measurements were collected from the next pasture in the paddock rotation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations